Pengembangan Keterampilan Kolaborasi pada Anak Usia Dini melalui Permainan Tradisional - Sewi, Rima Mustika; Mailasari, Dewi Ulya (PIAUD Universitas Islam Negeri Sunan Kudus, 2020)
This paper aims to describe the development of collaboration skills in early childhood through traditional games of bakiak, dhakon, and cublak-cublak suweng. This paper is absed on research using a qualitative approach and field research, where the researcher goes directly to the field to find the data. Data collection techniques were carried out by observing 24 students in a kindergarten, and 2 teachers who played the traditional games together, and by interviewing the two teachers and three participants. The results showed that the development of collaboration skills in early childhood through traditional games of bakiak, dhakon, cublak-cublak suweng was supported by the characteristics of games that were fun, challenging, familiar, and carried out together. The manifestation of the development aspects of collaboration in the traditional games is by fostering participation, patience, communication, solidarity, and self-confidence. These five aspects are important in supporting collaboration skills in children in the future.